Assessing and understanding the environmental changes in the Doubegue watershed (Burkina Faso) by combining temporal study of land use changes and stakeholders' knowledge. - Robert, Elodie (Geographical Journal, 2017)
Since the 1980s, the Bagre region (Burkina Faso) has witnessed significant environmental changes mainly due to anthropogenic causes (arrival of new population groups, demographic increase, reservoir creation, exacerbation of conflict linked to land ownership, and land and agrarian reform), and secondarily to climatic perturbations. For a comprehensive understanding of these environmental changes, and their causes and impacts in the Doubegue watershed, it is necessary to combine different analytical tools. An original methodology, which combines remote sensing and field survey, is proposed. A temporal study of land use change was conducted to identify areas at risk and ongoing processes. At the same time, a survey was carried out to study the local population's knowledge concerning changes to the resources of vegetation, water and soil. The analysis of a time series of satellite images reveals environmental changes mainly in the central area of the watershed, since the 1990s in particular, with an increase in cropped and bare soils. The survey also highlights reduction in vegetation cover, a decrease in soil quality and changes in the river system. In addition, stakeholders link the degradation of vegetation cover to changes in the river system. Finally, to reduce degradation of resources (vegetation, water and soil), actions are being developed and/or sought by the population and by organisations in the region.